Risk factors for unexpected death in patients identified by a communication and resolution program - Lodato, Peter; Goldstein, Neal D.; Mapp, Alexandra M.; Gbadebo, Adebayo; Pearlman, Stephen A. (Frontiers in Health Services, 2025)
Many patients experience unexpected harm while receiving healthcare, with a lasting impact on patients, families, and caregivers. Communication and Resolution Programs are being adopted with increased frequency, as a more systematic, transparent, and equitable approach to these unexpected outcomes. The aim of this study was to identify whether demographic factors played a role in identifying patients with unexpected death, as managed in our CRP. This nested case-controlled compared 236 patients who experienced an unanticipated death with 2,360 controls who died expectedly over a 10-year period. Patients with unexpected death were more likely to be Black (AOR 2.18 95% CI 1.01–4.68), higher comorbidity burden (AOR 1.07 per additional co-morbidity, 95% OR 1.01–1.14), and a lower Relative Expected Mortality (AOR: 5.39; 95% CI: 1.76–16.55). Awareness of these demographic risk factors for unexpected mortality may lead to changes in how these patients are evaluated and treated. Communication and Resolution Programs can be used to identify the patients at the highest risk for unexpected outcomes.